The synergistic extract of Zophobas atratus and Tenebrio molitor regulates neuroplasticity and oxidative stress in a scopolamine-induced cognitive impairment model - Tran, Ngoc Buu; Lee, Haesung; Ji, Myoung-Geun; Ngo Hoang, Long; Lee, Sook-Jeong (Frontiers in Aging Neuroscience, 2025)
IntroductionNeurodegenerative disorders, such as Alzheimer’s disease, arise from neuroinflammation, which leads to cognitive and memory impairment. Scopolamine is commonly used to induce cognitive and memory deficits in mouse models.AimsThis study investigated the neuroprotective potential of a Zophobas atratus (Za) and Tenebrio molitor (Tm) extract mixture (ZaTm mixture) in mitigating scopolamine-induced cognitive and memory deficits in mice.ResultsBehavioral assessments, including the Morris water maze, Y-maze, and light/dark tests, demonstrated that the ZaTm mixture significantly enhanced memory and cognitive function in treated mice. Furthermore, the ZaTm mixture restored the disrupted expression of choline acetyltransferase and acetylcholinesterase in the hippocampi of scopolamine-treated mice. Additionally, scopolamine-induced glutamatergic/GABAergic dysfunction was markedly improved following treatment with the ZaTm mixture. The extract also exhibited neuroprotective effects by enhancing the activity of antioxidants, such as glutathione and malondialdehyde, and key enzymes, including catalase and superoxide dismutase. Moreover, it effectively inhibited senescence in the hippocampus by modulating the AMPK/SIRT and BDNF-Akt/mTOR signaling pathways.DiscussionThis study highlights the promising potential of the ZaTm extract mixture as a novel therapeutic agent and functional food for the prevention and treatment of Alzheimer’s disease and other neurodegenerative disorders.